Combined-cycle hydropower systems - The potential of applying hydrokinetic turbines in the tailwaters of existing conventional hydropower stations - Liu, Y.; Packey, Daniel (Elsevier Science Ltd, 2013)
This paper focuses on discussing the potential and feasibility of increasing hydropower production by installing hydrokinetic turbines behind existing conventional hydropower stations to establish “combined-cycle hydropower system (CCHS)”. The CCHS will capture additional power from the energyremaining in water currents exiting dams. There are two modes of CCHS. The hydrokinetic turbine can be located directly behind the turbine of existing conventional hydropower plant or it can be placed at sites in the vicinity of powerhouse. The challenges and advantages associated with the CCHS are discussed in this paper. Although the technology of CCHS is still in its research and development phrase, not yet reaches mature and economically feasible; it is believed that it possesses significant potential to produce additional clean hydropower in the large-scale. It may become additional promising way of generating clean energy to mitigate climate change.